1990
DOI: 10.1111/j.1651-2227.1990.tb11354.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Carnitine Level in Phenylketonuric Children under Dietary Control in Greece

Abstract: Although total, free and esterified carnitine blood levels were found to be low (p less than 0.001) in phenylketonuric patients under dietary treatment compared to controls, no clinical signs of carnitine deficiency were noticed. Exclusion from the PKU diet of nutrients rich in carnitine has been suggested. Supplementation of the diets with carnitine or preferably enrichment of the PKU formulas with carnitine will rectify the restriction of extrinsic carnitine in PKU dietary treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Graphs show the Pearson correlation coefficient and probabilities Cell Mol Neurobiol (2009) 29:211-218 215 phenylketonuric patients, and thereafter investigated the relationship between serum L-carnitine deficiency and the oxidative stress process observed. We first observed that serum L-carnitine levels were significantly reduced in well-treated PKU patients with normal plasma Phe levels, but not in patients with poor compliance to the diet (with high Phe levels), reinforcing previous findings of other investigators (Schulpis et al 1990;Vilaseca et al 1993). Also, a positive correlation between serum Phe levels and serum L-carnitine levels was observed.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Graphs show the Pearson correlation coefficient and probabilities Cell Mol Neurobiol (2009) 29:211-218 215 phenylketonuric patients, and thereafter investigated the relationship between serum L-carnitine deficiency and the oxidative stress process observed. We first observed that serum L-carnitine levels were significantly reduced in well-treated PKU patients with normal plasma Phe levels, but not in patients with poor compliance to the diet (with high Phe levels), reinforcing previous findings of other investigators (Schulpis et al 1990;Vilaseca et al 1993). Also, a positive correlation between serum Phe levels and serum L-carnitine levels was observed.…”
Section: Discussionsupporting
confidence: 88%
“…This diet is mainly made up essentially of vegetables and fruits (poor in Phe) and provides the minimal amounts of animal products appropriate for normal development growth, while keeping plasma Phe levels within normal (Giovanini et al 2007). Since approximately 75% of L-carnitine content in human body is derived from the diet mainly from products of animal origin, PKU patients under dietary treatment are potentially prone to develop L-carnitine deficiency (Schulpis et al 1990;Vilaseca et al 1993). Moreover, some studies have demonstrated that special restricted diets may lead to a decrease of the antioxidant status in some inborn errors of metabolism (Artuch et al 2004;van Backel et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides acting in the bioenergetic process, many studies have reported antioxidant, antiradical, and antiperoxidative effects for L-carnitine due to different mechanisms (Ferrari et al 1988;Bertelli et al 1994;Gülçin et al 2006). Since the main dietary sources of L-carnitine are milk and red meat, secondary L-carnitine deficiency may be a consequence of the protein-restricted diet (Schulpis et al 1990). Therefore, it was also postulated that supplementation of this compound may be considered as an adjuvant therapy for PKU (Sitta et al 2009b).…”
Section: Oxidative Stress In Pku Patientsmentioning
confidence: 99%
“…The restriction of protein-rich foods in patients with organic acidaemias involves the risk of a concomitant restriction in the intake of important nutrients such as vitamins, minerals, Arachidonic acid 6.3 (2.9−9) 7.0 (4.8−9.4) 7.6 (6.5−10.0) 5.6 (2.9−9.7) 7.35 ( (Rottoli et al 1985;Sanjurjo et al 1994;Schulpis et al 1990). In addition, and due to enzymatic competition, a diet with a high proportion of n -6 fatty acids may secondarily affect the status of the n -3 fatty acid family.…”
Section: Discussionmentioning
confidence: 99%